2014
DOI: 10.1038/jcbfm.2014.46
|View full text |Cite|
|
Sign up to set email alerts
|

Determination of [11C]PBR28 Binding Potential in vivo: A First Human TSPO Blocking Study

Abstract: Positron emission tomography (PET) targeting the 18 kDa translocator protein (TSPO) is used to quantify neuroinflammation. Translocator protein is expressed throughout the brain, and therefore a classical reference region approach cannot be used to estimate binding potential (BP ND ). Here, we used blockade of the TSPO radioligand [ 11 C]PBR28 with the TSPO ligand XBD173, to determine the non-displaceable volume of distribution (V ND ), and hence estimate the BP ND . A total of 26 healthy volunteers, 16 high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 22 publications
8
133
0
Order By: Relevance
“…The in vivo specificity for this tracer has also been shown by others in the rat, 12 monkey, 4,33 and human. 34 The increase in PBR28 uptake with age is in agreement with the expectations for a TSPO ligand designed to quantify microglial activation. Aging is known to lead to changes in the microglial phenotype with a shift toward a more activated state; the microglia tend to become larger and more complex, with several changes in antigen expression.…”
Section: Discussionsupporting
confidence: 78%
“…The in vivo specificity for this tracer has also been shown by others in the rat, 12 monkey, 4,33 and human. 34 The increase in PBR28 uptake with age is in agreement with the expectations for a TSPO ligand designed to quantify microglial activation. Aging is known to lead to changes in the microglial phenotype with a shift toward a more activated state; the microglia tend to become larger and more complex, with several changes in antigen expression.…”
Section: Discussionsupporting
confidence: 78%
“…TSPO is also expressed in astrocytes; however, immunohistochemistry performed in a nonhuman primate brain after LPS administration confirmed that TSPO expression occurred mainly in activated microglia (32). To estimate the nonspecific binding contribution to [ 11 C]PBR28 V T , a blocking study with TSPO agonist XBD173 in humans confirmed that [ 11 C]PBR28 V T largely constitutes specific binding to TSPO (44). Thus, with the current imaging paradigm, the neuroimmune response to LPS can be quantitatively measured in vivo with [ 11 C]PBR28 and PET, in association with peripheral inflammation and sickness symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…Because there is no brain region devoid of TSPO expression (65,66), metabolite-corrected arterial plasma measurements of radioligand concentration are necessary for accurate in vivo quantification of binding. To overcome variability that may be associated with the arterial measurements (27,67), relative measures of binding, such as distribution volume ratios (DVRs), have been proposed (22).…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%